2014
DOI: 10.1530/joe-13-0259
|View full text |Cite
|
Sign up to set email alerts
|

Nandrolone decanoate inhibits gluconeogenesis and decreases fasting glucose in Wistar male rats

Abstract: The use of anabolic-androgenic steroids to improve physical performance or appearance has increased notably. The doses used are 10-to 100-fold higher than the therapeutic dose (TD), and this abuse can cause several side effects. Glucose metabolism is significantly affected by anabolic-androgenic steroid abuse, but studies about glycemic regulation during fasting are scarce. There are some evidences showing that testosterone can antagonize glucocorticoids action, which are crucial to glucose production during f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 36 publications
(37 reference statements)
1
22
0
4
Order By: Relevance
“…Interestingly, in an experimental study on male rats, therapy with supraphysiologic androgen doses lead to increased insulin resistance. 8 Consistently, a previous study showed reduced glucose tolerance among male powerlifters who were current AAS abusers and even development of T2D, during AAS abuse, has been reported. 9,10 Thus, increased as well as decreased plasma concentrations of androgens may impair insulin sensitivity in men.…”
Section: Introductionsupporting
confidence: 71%
“…Interestingly, in an experimental study on male rats, therapy with supraphysiologic androgen doses lead to increased insulin resistance. 8 Consistently, a previous study showed reduced glucose tolerance among male powerlifters who were current AAS abusers and even development of T2D, during AAS abuse, has been reported. 9,10 Thus, increased as well as decreased plasma concentrations of androgens may impair insulin sensitivity in men.…”
Section: Introductionsupporting
confidence: 71%
“…A Blood Glucose Monitoring System (ReliOn ® , Prime) was used to measure BGL before and 4 times at 30 min intervals after oral administration of 10% glucose solution (1 g/10 ml/ kg) as reported (Frankenfeld et al, 2014). …”
Section: Methodsmentioning
confidence: 99%
“…Steroid and vehicle were administered by a single intramuscular injection in the hind limb once a week for 8 wk. We have previously reported that this treatment was effective, decreasing testicular weight and increasing serum testosterone levels in male Wistar rats [12], [13]. One week after the last injection, the rats were killed by decapitation, and trunk blood was immediately collected.…”
Section: Methodsmentioning
confidence: 99%